Diamond and related nanostructures - Nagy, Csaba Levente; Diudea, Mircea Vasile (Carbon Materials: Chemistry and Physics, 2013)
Over the past twenty years, the field of carbon structures has been invigorated by the discovery of fullerenes and carbon nanotubes. These nano-structured carbons have attracted a tremendous interest in the fundamental properties of discrete carbon molecules, leading to the discovery of novel complex crystalline and quasi-crystalline materials. As a consequence, a variety of applications have been developed, including technical and bio-medical materials and miniaturized tools. Diamond and Related Nanostructures focuses on the advances in the area of diamond-like carbon nanostructures (hyper-structures built from fullerenes and/or carbon nanotube junctions) and other related carbon nanostructures. Each chapter contributes to the topic from different fields, ranging from theory to synthesis and properties investigation of these new materials. This volume provides a source of inspiration and understanding to advanced undergraduates, graduates, and researchers in the fields of Physics, Graph Theory, Crystallography, Computational and Synthetic Chemistry.